Factors Contributing to the Difficulties in Teaching and Learning of Computer Programming: A Literature Review - Cheah, Chin Soon (Contemporary educational technology, 2020)
This paper reviews the literature relating to the factors that contribute to the difficulties in learning of computer programming. Programming has been a difficult subject to learn and master even at the early stage of education. It has been a global problem and continues to worsen at the local level. Although, there are many education tools available to complement the teaching and learning of computer programming. The problem persists until present day. Even at the initial stage of computer introduction courses, there were high failure rates and high drop out. One of the rationalism behind this scenario is from the students’ lack of problem solving abilities. However, the problem does not only lie within the students’ level of efficacy. It involves the effective use of teaching and learning material as well. Therefore, the focus of this review is on the factors concerning the students learning method and the effectiveness of the teaching material. Based on plethora of literature review, it is vital that these two aspects need to be consider simultaneously to overcome the difficulties of learning computer programming. A much more comprehensive, effective and universal teaching and learning tools need to be design to address the severity of this problem.